Performance outcomes from a DMEK peeling and preparation wet lab - Sajjad Ahmad; Vito Romano; Mohit Parekh; Stefano Ferrari; Alessandro Ruzza; Matteo Airaldi; Alexander George Wallace (BMJ Open Ophthalmology)
Objective To evaluate the Descemet membrane endothelial keratoplasty (DMEK) preparation performance of trainee surgeons in an ex vivo human donor cornea DMEK wet lab simulation setting.Methods Human donor corneoscleral rims unsuitable for transplantation were obtained from Moorfields Lions Eye Bank. At the wet lab, graft stripping was performed by scoring the peripheral endothelium. The trypan blue positive cells (TBPC) and cell density (cells/mm2—reticule count) were counted manually before and after stripping. The procedural time, peripheral and central tears and complete peel-off were also recorded and analysed.Results Eight trainee surgeons attended the wet lab each attempting three DMEKs. Between the first and last attempts a significant decrease was seen in the procedural time (17.6 min vs 10.6 min (p<0.05)) and the TBPC % (12.9% vs 3.8% (p<0.05)). The percentage of tears peripherally and centrally also reduced between the first and the last trials (50% vs 13% (p=0.2226) and 38% vs 0% (p=0.1327)). A significant correlation was found between longer peeling times and higher TBPC % (p<0.001) with a 0.7% endothelial mortality increase for each additional minute required to complete the peel.Conclusions DMEK wet labs provide a controlled risk-free learning opportunity for trainee surgeons to improve confidence and competence. Wet labs improve the success rate of DMEK graft preparation as well as flatten the learning curve. This emphasises the importance of continued support for the expansion of this valuable learning resource, promoting wider uptake of DMEK surgery.